Mechanisms of Resistance to Prostate-Specific Membrane Antigen-Targeted Radioligand Therapy in a Mouse Model of Prostate Cancer - Andreea D. Stuparu; Joseph Capri; Catherine Meyer; Thuc Le; Susan Evans‐Axelsson; Kyle Current; Mark Lennox; Christine E. Mona; Wolfgang P. Fendler; Jérémie Calais; Matthias Eiber; Magnus Dahlbom; et al. (2020)
Prostate-specific membrane antigen (PSMA)–targeted radioligand therapy (RLT) is effective against prostate cancer (PCa), but all patients relapse eventually. Poor understanding of the underlying resistance mechanisms represents a key barrier to development of more effective RLT. We investigate the proteome and phosphoproteome in a mouse model of PCa to identify signaling adaptations triggered by PSMA RLT. Methods: Therapeutic efficacy of PSMA RLT was assessed by tumor volume measurements, time to progression, and survival in C4-2 or C4-2 TP53−/− tumor-bearing nonobese diabetic scid γ-mice. Two days after RLT, the proteome and phosphoproteome were analyzed by mass spectrometry. Results: PSMA RLT significantly improved disease control in a dose-dependent manner. Proteome and phosphoproteome datasets revealed activation of genotoxic stress response pathways, including deregulation of DNA damage/replication stress response, TP53, androgen receptor, phosphatidylinositol-3-kinase/AKT, and MYC signaling. C4-2 TP53−/− tumors were less sensitive to PSMA RLT than were parental counterparts, supporting a role for TP53 in mediating RLT responsiveness. Conclusion: We identified signaling alterations that may mediate resistance to PSMA RLT in a PCa mouse model. Our data enable the development of rational synergistic RLT-combination therapies to improve outcomes for PCa patients.